A case of recanalised umbilical vein thrombosis - Yang, Caroline M.; Jayewardene, Ishanth Devinda (International Surgery Journal, 2026)
A case of a 55 year old woman with recanalised umbilical vein thrombosis in a patient with gastritis who does not have liver cirrhosis or portal hypertension. This patient had presented with mild nausea and acute onset of epigastric pain. CT abdomen and pelvis had demonstrated this finding of a recanalised umbilical vein with thrombus formation, along with some thickening of the gastric antrum with mild surrounding fat stranding suggestive of gastritis. The patient underwent an inpatient gastroscopy to rule out malignancy in context of these findings, which only demonstrated some healed gastric ulcers. Histopathology report described chronic gastritis and intestinal metaplasia, no evidence of established malignancy. This is an unusual case that highlights that recanalisation of the umbilical vein could occur without portal hypertension. This may have been a spontaneous event or could have been caused by local inflammation such as gastritis.